Front Cover: Label‐free spectroscopic tissue characterization using fluorescence excitation‐scanning spectral imaging (J. Biophotonics 2/2020). Issue 2 (3rd February 2020) - Favreau, Peter F.; Deal, Joshua A.; Harris, Bradley; Weber, David S.; Rich, Thomas C.; Leavesley, Silas J.
Abstract : A false‐colored and merged image of fresh, ex vivo rat kidney acquired using an excitation‐scanning hyperspectral imaging system. The spectral image was acquired using excitation wavelengths from 360 to 550 nm. Colors represent principal components extracted from a spectral image cube featuring no added labels or markers. Further details can be found in the article by Peter F. Favreau, Joshua A. Deal, Bradley Harris, et al. (e201900183 ). Abstract : A false‐colored and merged image of fresh, ex vivo rat kidney acquired using an excitation‐scanning hyperspectral imaging system. The spectral image was acquired using excitation wavelengths from 360 to 550 nm. Colors represent principal components extracted from a spectral image cube featuring no added labels or markers. Further details can be found in the article by Peter F. Favreau, Joshua A. Deal, Bradley Harris, et al. (e201900183 ).